2010
DOI: 10.1542/peds.2009-3067
|View full text |Cite
|
Sign up to set email alerts
|

MRI and Withdrawal of Life Support From Newborn Infants With Hypoxic-Ischemic Encephalopathy

Abstract: The majority of deaths in infants with hypoxic-ischemic encephalopathy (HIE) follow decisions to withdraw life-sustaining treatment. Clinicians use prognostic tests including MRI to help determine prognosis and decide whether to consider treatment withdrawal. A recently published meta-analysis provided valuable information on the prognostic utility of magnetic resonance (MR) biomarkers in HIE and suggested, in particular, that proton MR spectroscopy is the most accurate predictor of neurodevelopmental outcome.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 75 publications
0
26
0
Order By: Relevance
“…In their meta-analysis, Thayyil and coworkers found that deep gray matter magnetic resonance biomarkers (especially measuring lactate/acetyl aspartate ratio) have good accuracy for predicting adverse outcome in neonatal encephalopathy [3]. Professor Wilkinson appropriately criticized this meta-analysis and suggested to perform an individual patient data meta-analysis [4], a challenge we accepted. The study protocol was published last year in Systematic Reviews [5].…”
Section: Correspondence/findingsmentioning
confidence: 99%
“…In their meta-analysis, Thayyil and coworkers found that deep gray matter magnetic resonance biomarkers (especially measuring lactate/acetyl aspartate ratio) have good accuracy for predicting adverse outcome in neonatal encephalopathy [3]. Professor Wilkinson appropriately criticized this meta-analysis and suggested to perform an individual patient data meta-analysis [4], a challenge we accepted. The study protocol was published last year in Systematic Reviews [5].…”
Section: Correspondence/findingsmentioning
confidence: 99%
“…Real-time assessment of DWI and GRE images is useful to analyze the injury pattern and add additional sequences such as MRA, MRV and MR spectroscopy to a b c d MRI plays an important role in assessing response to therapeutic hypothermia and other treatment options [34]. MR imaging can also identify factors predicting poor patient outcome such as larger size of infarcts, involvement of critical areas, absolute decrease in NAA values in basal ganglia, low apparent diffusion coefficients in the non-infarcted brain and abnormal DWI signal in the corticospinal tracts [23,[35][36][37][38][39] withdrawal of life support and can be used as a patient selection tool for advanced treatment options like stem cell therapy [40,41].…”
Section: Perinatal Sinovenous Thrombosismentioning
confidence: 99%
“…The suggestion that Lac/NAA might support early clinical decisions was criticized for several reasons [4]. Although based on available studies, the validity of the meta-analysis and the generalizability of the results were questioned [4].…”
Section: Introductionmentioning
confidence: 99%
“…Although based on available studies, the validity of the meta-analysis and the generalizability of the results were questioned [4]. It was suggested that the spectrum of the included patients was too broad, including very mildly (Sarnat 1) and very severely (Sarnat 3) affected patients; unclear selection criteria could undermine generalizability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation